Abbreviations Used in Social Media Named X by Indonesian Comedian - Handayani, Wia; Simatupang, Ervina CM (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to investigate how Indonesian comedians use abbreviations on the social media platform X (formerly Twitter). This research focuses on the ways in which comedians from Indonesia, in particular, use abbreviations to communicate and express themselves on social media. The various forms of abbreviations and their underlying meanings are examined. The data source for this study was the social media platform X, and it employed a descriptive-qualitative methodology. Numerous abbreviations, such as acronyms, contractions, blends, and initialisms, are revealed by the research. In the context of the Indonesian comic community on social media known as X, examples are given to highlight their meanings and ramifications. Based on the type of abbreviation procedure, the result indicates that thirty (30) data are classified. There are 15 data containing an initialism, 6 data containing an acronym, 6 data containing contraction, and 3 data containing blends. Keywords: Abbreviations, Indonesian Comedians, Meanings, Social Media